(untitled) (Journal of the College of Basic Education, 2026)
The importance of this study stems from examining the effect of mini-circuit training at maximum anaerobic effort, due to its significant role in developing the physical and skill-related abilities of youth handball players, particularly in the fast break, which requires speed, explosive strength, and high agility. The research problem lies in the relative deficiency in some of these abilities among players, often resulting from reliance on traditional training programs that do not meet the demands of high-speed performance and the time pressure of matches. The results indicated that applying these exercises contributed to significant improvements in movement speed, speed-strength, speed endurance, and fast break efficiency in favor of the experimental group. This can be attributed to the design of the exercises in short-duration, high-intensity stations with small-sided tactical situations that simulate actual match conditions, leading to an integrated development of the players’ physical, technical, and tactical performance. It is recommended to incorporate these exercises regularly into training programs while considering intensity progression and variation in tactical situations to achieve optimal results in team and offensive performance.